2013
DOI: 10.1080/02626667.2013.783215
|View full text |Cite
|
Sign up to set email alerts
|

Vertical heterogeneities of hydraulic aquitard parameters: preliminary results from laboratory andin situmonitoring

Abstract: A borehole is developed in a shallow multi-layered aquifer and used to derive the porosity, specific storage and hydraulic conductivity of the aquitard. Local values of hydrodynamical parameters are estimated from petrophysical analysis of core samples, and the empirical relationship between porosity and permeability. Vertical diffusivity is determined from the response of the aquitard to a loading cyclic signal using pressure records at different depths. Hydraulic conductivities deduced from the petrophysical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Leakage can exist across an aquitard, which can strongly affect the drawdown response of an underlying confined aquifer during groundwater pumping ( Jacob, 1946). Aquitard hydrogeology has been well documented, with the majority of the research concentrated on clay-rich aquitards (Desaulniers et al, 1981;Hendry et al, 2004;Hiscock and Tabatabai Najafi, 2011;Larroque et al, 2013;Machado et al, 2007;Wiese and Nützmann, 2011). Having a greater permeability than clay-rich aquitards, silty aquitards have a greater average linear velocity and therefore greater potential for contaminants to reach the aquifer faster.…”
Section: Chloride Dispersion Across Silt Deposits In a Glaciated Bedrmentioning
confidence: 99%
“…Leakage can exist across an aquitard, which can strongly affect the drawdown response of an underlying confined aquifer during groundwater pumping ( Jacob, 1946). Aquitard hydrogeology has been well documented, with the majority of the research concentrated on clay-rich aquitards (Desaulniers et al, 1981;Hendry et al, 2004;Hiscock and Tabatabai Najafi, 2011;Larroque et al, 2013;Machado et al, 2007;Wiese and Nützmann, 2011). Having a greater permeability than clay-rich aquitards, silty aquitards have a greater average linear velocity and therefore greater potential for contaminants to reach the aquifer faster.…”
Section: Chloride Dispersion Across Silt Deposits In a Glaciated Bedrmentioning
confidence: 99%
“…Aquitard properties, such as hydraulic conductivity, and their variability can be determined by fluid pressure measurements within the aquitard using in situ vibrating wire pressure transducers [6,7], although hydraulic conductivity measurements can increase with the scale of measurement [8,9]. When combined with the gradient of fluid pressure using Darcy's law, the vertical flow direction and rate can be determined.…”
Section: Introductionmentioning
confidence: 99%
“…In these Regions S and W, water (i.e., surface and ground water) is stored year round regardless of changes in seasonal climate (Figures and ) in part due to the formation with higher clay content, which typically shows lower hydraulic conductivities (e.g. Larroque et al, ; Yu et al, ) (Figure ). These observations revealed that the water table at both CROMO sites is not laterally continuous but perched by the surrounding lithology.…”
Section: Discussionmentioning
confidence: 99%